Constraints Management of Organic Farming: Evidence from Pokhara Metropolitan, Nepal (Victoria Journal of Management, 2025)
Organic agriculture has become an important concept within the Nepali agricultural sector, particularly in the hills and mountainous regions where traditional farming practices closely resemble organic methods. This study aims to identify the challenges faced by organic farmers in Pokhara, focusing on the availability of organic inputs, pest management, and market linkages. Data was collected through surveys, field observations, and interactions with 197 farmers, using structured questionnaires. A descriptive research design has been used to assess the challenges faced by organic farmers in Pokhara, Nepal. The study focused on issues such as access to organic inputs, pest management, and market linkages, with data analyzed using descriptive and inferential statistics (One-way ANOVA, T-tests) and reliability tested through Cronbach’s alpha. SPSS software was used for data analysis, ensuring a comprehensive and reliable examination of the constraints affecting organic farming practices in the region. This study examined the key constraints faced by organic farmers in Pokhara, focusing on access to organic inputs, pest and disease management, and market linkages. Results indicated that better access to organic inputs positively impacted farming practices and pest control, while market linkages were less influential on success. Result shows significant challenges in input availability, pest management, and market access, with gender differences showing slightly better outcomes for female farmers. The study highlights the need for improved government support, better pest management strategies, and enhanced market access to foster the growth of organic farming in Pokhara.